Pemasaran Produk Inovatif Daur Ulang dengan Konsep Green Branding di Kalangan Milenial - Muis, Muhammad; Zaitun, Zaitun; Zebar, A; Tommy Maulidyanto, Muhammad; Andi, Andi; Sugianto, Sugianto (ABDIMASKU : Jurnal Pengabdian Masyarakat UTND, 2025)
The purpose of this community service activity is to empower partners in building an environmentally friendly brand image (green branding) to enhance the competitiveness of their products in a market increasingly aware of sustainability issues. This community service activity was carried out using a participatory and collaborative approach, actively involving partners from the planning stage to evaluation. The partners in this activity are micro-entrepreneurs or communities of recycled product artisans who have potential but still face limitations in marketing strategies, particularly in attracting young consumers such as millennials. This community service activity successfully enhanced the understanding and skills of participants, especially millennials, in utilizing green branding strategies as a marketing approach for recycled products. Participants not only gained conceptual knowledge about the importance of sustainability in business but also implemented it through hands-on practice in product creation and educational digital campaigns. The improvement in understanding from pre-test to post-test, as well as the achievement of targets in social media use, demonstrates the success of the training methods applied. In addition to individual improvement, this activity also encouraged the formation of new business groups that market environmentally friendly products online. This activity successfully enhanced the understanding and skills of participants, particularly millennials, in leveraging green branding strategies as a tool for marketing recycled products. The results of the training, reflected in the improvement of understanding through pre-test and post-test scores, as well as the achievement of targets in social media use, indicate the effectiveness of the applied methods